Anti-reflection and anti-reflection film with environmental stability, preparation method of anti-reflection and anti-reflection film and optical element

By using a stacked interference film and a titanium dioxide alumina film in the impermeable and reducing film, combined with hydrothermal treatment and vacuum drying technology, the problem of poor environmental stability of the impermeable and reducing film in the prior art is solved, and the reflectivity is achieved. And it has stable properties for organic pollution.

CN119200053APending Publication Date: 2024-12-27GUANGCHI SEMICON TECH (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310766192.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing anti-reflection films have poor stability in environmental testing and are easy to interact with the volatile gases of organic binders used in the lens module assembly process, resulting in a significant increase in reflectivity and cannot meet actual production needs.

Method used

The interference films are arranged in at least one layer, and the outermost layer is provided with an alumina film containing titanium dioxide. The interference film is deposited by atomic layer deposition technology, and vacuum drying is carried out after hydrothermal treatment to form an increase in permeability with excellent environmental stability. membrane.

Benefits of technology

The environmental stability of the reflectivity is maintained below 0.1%, and the reflectivity changes less after the organic matter pollution test, and the excellent environmental stability is continuously maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200053A_ABST
    Figure CN119200053A_ABST
Patent Text Reader

Abstract

The invention provides an anti-reflection and anti-reflection film with environmental stability, a preparation method thereof and an optical element, the anti-reflection and anti-reflection film comprises at least one layer of interference film which is laminated, and an aluminum oxide film containing titanium dioxide is laminated on the surface of the interference film on the outermost layer. The anti-reflection and anti-reflection film with the environmental stability can well pass an environmental test, the reflectivity is always kept to be 0.1% or below, the reflectivity change of the anti-reflection and anti-reflection film is small after an organic matter pollution test, the reflectivity is continuously kept to be 0.1% or below, and the anti-reflection and anti-reflection film has the excellent environmental stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical devices, and relates to an anti-reflection film with environmental stability, and in particular to an anti-reflection film with environmental stability, a preparation method thereof, and an optical element. Background Art

[0002] Anti-reflection and anti-reflection coatings (AR Coatings) are widely used in the fields of lenses and displays. The AR Coatings currently prepared by atomic layer deposition (ALD) have low visible light reflectivity and large bandwidth, but poor environmental stability and are difficult to pass environmental tests. In addition, after the organic adhesive used in the lens module assembly process evaporates, its gas molecules will interact with the AR Coatings in the prior art, causing a significant increase in reflectivity. The AR Coatings in the prior art have poor environmental stability.

[0003] CN107793041A discloses a method for preparing a tempered glass with a wear-resistant aluminum oxide coating layer, comprising the steps of: a) washing the tempered glass substrate with an organic solvent and deionized water in turn, and then drying; b) growing a magnesium oxide film layer with a polycrystalline structure on the tempered glass substrate using MOCVD technology; c) epitaxially growing an aluminum oxide film layer on the magnesium oxide film layer using ALD technology; d) uniformly coating the surface of the aluminum oxide film layer with titanium dioxide sol, and then curing to form a low-refractive-index titanium dioxide light-enhancing coating layer. The magnesium oxide film and aluminum oxide film formed by the invention are both highly dense, can enhance the hardness of the tempered glass surface, improve the scratch resistance and wear resistance, and the film has good uniformity and the thickness can be precisely controlled; the top layer of the low-refractive-index titanium dioxide light-enhancing coating layer has a low refractive index, which greatly improves the light transmittance of the tempered glass. However, the wear-resistant aluminum oxide coating layer will interact with the volatile gas of the organic adhesive used in the lens module assembly process, thereby causing the reflectivity of the wear-resistant aluminum oxide coating layer to increase significantly.

[0004] CN107337356A discloses a method for preparing a composite anti-reflection film of polytetrafluoroethylene and alumina atomic layer, which first uses an electron beam evaporation method to deposit a dense polytetrafluoroethylene layer on a transparent or translucent substrate, and then deposits a porous polytetrafluoroethylene nanorod layer to obtain a double-layer polytetrafluoroethylene film; then the obtained double-layer polytetrafluoroethylene film is placed in an atomic layer deposition device to deposit an alumina coating layer. The composite film has an excellent anti-reflection and anti-transmittance effect on multi-angle incident light in the visible light range; at the same time, due to the special hydrophobic and oleophobic surface properties and chemical stability of polytetrafluoroethylene, the anti-reflection film has a good self-cleaning effect and excellent biocompatibility. However, the environmental stability of the composite anti-reflection film of polytetrafluoroethylene and alumina atomic layer still cannot meet the needs of actual production practice.

[0005] The AR films in the prior art have certain defects, such as difficulty in passing environmental tests and interaction with the volatile gas of the organic adhesive used in the lens module assembly process, which leads to a significant increase in reflectivity. Therefore, it is very important to develop a new type of environmentally stable AR film and its preparation method and optical element. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide an anti-reflection film with environmental stability, a preparation method thereof, and an optical element. The anti-reflection film with environmental stability provided by the present invention can pass environmental tests well, and the reflectivity is always maintained below 0.1%. After the organic pollution test, the reflectivity of the anti-reflection film changes little, and the reflectivity is continuously maintained below 0.1%. The anti-reflection film has excellent environmental stability.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprising at least one layer of stacked interference film, an aluminum oxide film containing titanium dioxide being stacked on the surface of the outermost interference film.

[0009] The anti-reflection and anti-reflection film with environmental stability provided by the present invention can pass environmental tests well, and the reflectivity is always kept below 0.1%. Moreover, after the organic pollution test, the reflectivity of the anti-reflection and anti-reflection film changes little, and the reflectivity is continuously kept below 0.1%. The anti-reflection and anti-reflection film has excellent environmental stability.

[0010] Preferably, the mass fraction of titanium dioxide in the aluminum oxide film is 1% to 10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] Preferably, the thickness of the aluminum oxide film is 30 to 40 nm, for example, it can be 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm or 40 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] Preferably, the thickness of each layer of the interference film is independently 5 to 50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Preferably, the anti-reflection and anti-reflection film includes four stacked interference films, and along the direction from away from the aluminum oxide film to close to the aluminum oxide film, the thickness of the four interference films are 5-15nm, 30-50nm, 1-10nm and 30-50nm respectively.

[0014] In the present invention, the thickness of the first interference film along the direction away from the aluminum oxide film to the direction close to the aluminum oxide film is 5 to 15 nm, for example, it can be 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm or 15 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] In the present invention, the thickness of the second interference film along the direction away from the aluminum oxide film to the aluminum oxide film is 30 to 50 nm, for example, it can be 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm or 50 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In the present invention, the thickness of the third interference film along the direction away from the aluminum oxide film to the direction close to the aluminum oxide film is 1 to 10 nm, for example, it can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In the present invention, the thickness of the fourth interference film along the direction away from the aluminum oxide film to the aluminum oxide film is 30 to 50 nm, for example, it can be 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm or 50 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In a second aspect, the present invention provides a method for preparing the anti-reflection and anti-reflection film according to the first aspect, the preparation method comprising:

[0019] The first deposition obtains at least one interference film, and the second deposition of an aluminum oxide film containing titanium dioxide is carried out on the surface of the outermost interference film. The film is dried after hydrothermal treatment to obtain an anti-reflection and anti-transmission film.

[0020] Preferably, the first deposition and the second deposition each independently comprise atomic layer deposition.

[0021] Preferably, the solution used in the hydrothermal treatment is water.

[0022] The water mentioned in the present invention includes ultrapure water.

[0023] Preferably, the pH of the solution used in the hydrothermal treatment is 5 to 8, for example, it can be 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.4, 7.6, 7.8 or 8, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the temperature of the hydrothermal treatment is 50-90° C., and the time is 10-40 min.

[0025] The temperature of the hydrothermal treatment in the present invention is 50-90°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] The time of the hydrothermal treatment in the present invention is 10 to 40 minutes, for example, it can be 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the drying comprises vacuum drying.

[0028] Preferably, the vacuum drying is carried out at a temperature of 0 to 85° C. and for a time of 10 to 60 minutes.

[0029] The temperature of vacuum drying in the present invention is 0-85°C, for example, it can be 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 50°C, 60°C, 70°C, 80°C or 85°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] The vacuum drying time in the present invention is 10 to 60 minutes, for example, it can be 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the vacuum degree of the vacuum drying is less than 10Pa, for example, it can be 9.9Pa, 9.5Pa, 9.2Pa, 9Pa, 8.8Pa, 8.5Pa, 8.2Pa, 8Pa, 7Pa, 6Pa, 5Pa, 4Pa, 3Pa, 2Pa or 1Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:

[0033] Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film containing titanium dioxide is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 10-40 minutes in water with a pH of 5-8 and a temperature of 50-90°C, vacuum drying is performed in an environment with a temperature of 0-85°C and a vacuum degree of less than 10Pa to obtain an anti-reflection and anti-transmission film.

[0034] In a third aspect, the present invention provides an optical element, comprising the anti-reflection and anti-reflection film described in the first aspect.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The anti-reflection and anti-reflection film with environmental stability provided by the present invention can pass environmental tests well, and the reflectivity is always kept below 0.1%. Moreover, after the organic pollution test, the reflectivity of the anti-reflection and anti-reflection film changes little, and the reflectivity is continuously kept below 0.1%. The anti-reflection and anti-reflection film has excellent environmental stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the structure of an anti-reflection and anti-reflection film with environmental stability in a specific embodiment of the present invention.

[0038] Figure 2 Graph showing the reflectivity of the anti-reflection and anti-reflection films of Example 1 and Comparative Example 1 after the environmental stability test as a function of wavelength.

[0039] Figure 3 The graph is a graph showing the variation of reflectivity with wavelength after the environmental stability test of the anti-reflection and anti-reflection films in Example 1, Example 10, Comparative Example 1 and Comparative Example 2.

[0040] Among them, 1-interference film; 2-titanium dioxide; 3-aluminum oxide film. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0042] In a specific embodiment, Figure 1 As shown, the present invention provides an anti-reflection and anti-reflection film with environmental stability, wherein the anti-reflection and anti-reflection film comprises at least one layer of stacked interference film 1, and an aluminum oxide film 3 containing titanium dioxide 2 is stacked on the surface of the outermost interference film 1.

[0043] Furthermore, the mass fraction of titanium dioxide 2 in the aluminum oxide film 3 is 1% to 10%.

[0044] Furthermore, the aluminum oxide film 3 has a thickness of 30-40 nm.

[0045] Furthermore, the thickness of each layer of the interference film 1 is independently 5 to 50 nm;

[0046] Furthermore, the anti-reflection and anti-reflection film includes four stacked interference films 1. Along the direction away from the aluminum oxide film 3 to close to the aluminum oxide film 3, the thicknesses of the four interference films 1 are 5-15nm, 30-50nm, 1-10nm and 30-50nm respectively.

[0047] Example 1

[0048] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprises four layers of interference films stacked, and the thicknesses of the four interference films from away from the aluminum oxide film to close to the aluminum oxide film are 10nm, 40nm, 5nm and 40nm respectively; an aluminum oxide film containing titanium dioxide with a thickness of 35nm is stacked on the surface of the outermost interference film, and the mass fraction of titanium dioxide in the aluminum oxide film is 5%;

[0049] The preparation method of the anti-reflection film comprises:

[0050] Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film containing titanium dioxide is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 25 minutes in water with a pH of 7 and a temperature of 70°C, vacuum drying is performed in an environment with a temperature of 40°C and a vacuum degree of 6Pa to obtain an anti-reflection and anti-transmission film.

[0051] Example 2

[0052] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprises four layers of interference films stacked, and the thicknesses of the four interference films from away from the aluminum oxide film to close to the aluminum oxide film are 8nm, 35nm, 8nm and 45nm respectively; an aluminum oxide film containing titanium dioxide with a thickness of 32nm is stacked on the surface of the outermost interference film, and the mass fraction of titanium dioxide in the aluminum oxide film is 8%;

[0053] The preparation method of the anti-reflection film comprises:

[0054] Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film containing titanium dioxide is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 18 minutes in water with a pH of 6 and a temperature of 80°C, vacuum drying is performed in an environment with a temperature of 60°C and a vacuum degree of 8Pa to obtain an anti-reflection and anti-transmission film.

[0055] Example 3

[0056] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprises four layers of interference films stacked, and the thicknesses of the four interference films from away from the aluminum oxide film to close to the aluminum oxide film are 12nm, 45nm, 3nm and 35nm respectively; an aluminum oxide film containing titanium dioxide with a thickness of 37nm is stacked on the surface of the outermost interference film, and the mass fraction of titanium dioxide in the aluminum oxide film is 3%;

[0057] The preparation method of the anti-reflection film comprises:

[0058] Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film containing titanium dioxide is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 32 minutes in water with a pH of 7.5 and a temperature of 60°C, vacuum drying is performed in an environment with a temperature of 20°C and a vacuum degree of 4Pa to obtain an anti-reflection and anti-transmission film.

[0059] Example 4

[0060] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprises four layers of interference films stacked, and the thicknesses of the four interference films from away from the aluminum oxide film to close to the aluminum oxide film are 5nm, 30nm, 10nm and 50nm respectively; an aluminum oxide film containing titanium dioxide with a thickness of 30nm is stacked on the surface of the outermost interference film, and the mass fraction of titanium dioxide in the aluminum oxide film is 10%;

[0061] The preparation method of the anti-reflection film comprises:

[0062] Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film containing titanium dioxide is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 10 minutes in water with a pH of 5 and a temperature of 90°C, vacuum drying is performed in an environment with a temperature of 85°C and a vacuum degree of 9.9Pa to obtain an anti-reflection and anti-transmission film.

[0063] Example 5

[0064] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprises four layers of interference films stacked, and the thicknesses of the four interference films from away from the aluminum oxide film to close to the aluminum oxide film are 15nm, 50nm, 1nm and 30nm respectively; an aluminum oxide film containing titanium dioxide with a thickness of 40nm is stacked on the surface of the outermost interference film, and the mass fraction of titanium dioxide in the aluminum oxide film is 1%;

[0065] The preparation method of the anti-reflection film comprises:

[0066] Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film containing titanium dioxide is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 40 minutes in water with a pH of 8 and a temperature of 50°C, vacuum drying is performed in an environment with a temperature of 0°C and a vacuum degree of 1Pa to obtain an anti-reflection and anti-transmission film.

[0067] Example 6

[0068] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, which is the same as that of Embodiment 1 except that the mass fraction of titanium dioxide in the aluminum oxide film is 0.5%.

[0069] Example 7

[0070] This embodiment provides an anti-reflection and anti-reflection film with environmental stability. Except that the mass fraction of titanium dioxide in the aluminum oxide film is 15%, the rest is the same as that of embodiment 1.

[0071] Example 8

[0072] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, which is the same as the first embodiment except that a 20 nm thick aluminum oxide film containing titanium dioxide is stacked on the surface of the outermost interference film.

[0073] Example 9

[0074] This embodiment provides an anti-reflection and anti-reflection film with environmental stability, which is the same as the first embodiment except that a 50 nm thick aluminum oxide film containing titanium dioxide is stacked on the surface of the outermost interference film.

[0075] Example 10

[0076] This embodiment provides an anti-reflection and anti-reflection film with environmental stability. Except that in the preparation method of the anti-reflection and anti-reflection film, after the hydrothermal treatment, the film is dried in an air environment at a temperature of 80° C., the rest is the same as that of Embodiment 1.

[0077] Comparative Example 1

[0078] This comparative example provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprises four layers of interference films stacked, and the thicknesses of the four interference films from away from the aluminum oxide film to close to the aluminum oxide film are 10nm, 40nm, 5nm and 40nm respectively; an aluminum oxide film with a thickness of 35nm is stacked on the surface of the outermost interference film;

[0079] The preparation method of the anti-reflection film comprises:

[0080] Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment is performed in water with a pH of 7 and a temperature of 70° C. for 25 minutes, it is dried in an air environment with a temperature of 80° C. to obtain an anti-reflection and anti-transmission film.

[0081] Comparative Example 2

[0082] This comparative example provides an anti-reflection and anti-reflection film with environmental stability, the anti-reflection and anti-reflection film comprises four layers of interference films stacked, and the thicknesses of the four interference films from away from the aluminum oxide film to close to the aluminum oxide film are 10nm, 40nm, 5nm and 40nm respectively; an aluminum oxide film with a thickness of 35nm is stacked on the surface of the outermost interference film;

[0083] The preparation method of the anti-reflection film comprises:

[0084] Atomic layer deposition is performed to obtain at least one interference film, and an aluminum oxide film is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 25 minutes in water with a pH of 7 and a temperature of 70°C, vacuum drying is performed in an environment with a temperature of 40°C and a vacuum degree of 6Pa to obtain an anti-reflection and anti-transmission film.

[0085] The environmental stability test and the organic pollution test were performed on the anti-reflection and anti-reflection films with environmental stability provided in Examples 1 to 10 and Comparative Examples 1 and 2, and the first average reflectivity of the anti-reflection and anti-reflection films after the environmental stability test and the second average reflectivity of the anti-reflection and anti-reflection films after the organic pollution test were obtained as shown in Table 1; the reflectivity curves of the anti-reflection and anti-reflection films in Example 1 and Comparative Example 1 after the environmental stability test as a function of wavelength were obtained as shown in Table 1. Figure 2 As shown; the reflectivity curves of the anti-reflection films in Example 1, Example 10, Comparative Example 1 and Comparative Example 2 after the environmental stability test are obtained as a function of wavelength are shown Figure 3 As shown;

[0086] The method of environmental stability test is: after placing the anti-reflection film in an environment with a temperature of 85°C and a humidity of 85% for 250 hours, the first average reflectivity is obtained by testing;

[0087] The method for testing organic contamination is as follows: placing the anti-reflection and anti-reflection film and 127.5 mg of organic adhesive in the same sealed container at a temperature of 80° C. for 1.5 hours, and then testing to obtain a second average reflectivity.

[0088] Table 1

[0089] First average reflectivity (%) Second average reflectivity (%) Example 1 0.03% 0.06% Example 2 0.05% 0.08% Example 3 0.04% 0.08% Example 4 0.04% 0.06% Example 5 0.02% 0.09% Example 6 0.13% 0.24% Example 7 0.57% 0.59% Example 8 0.18% 0.23% Example 9 0.19% 0.22% Example 10 0.12% 0.52% Comparative Example 1 0.13% 0.38% Comparative Example 2 0.22% 0.17%

[0090] From Table 1, Figure 1 and Figure 2 We can get:

[0091] (1) The anti-reflection and anti-reflection films with environmental stability provided in Examples 1 to 5 can pass environmental tests well, with a first average reflectivity lower than 0.1%, and the reflectivity of the anti-reflection and anti-reflection films changes little after the organic pollution test, and a second average reflectivity lower than 0.1%. The anti-reflection and anti-reflection films have excellent environmental stability;

[0092] (2) By comparing Example 1 with Examples 6 and 7, it can be seen that the mass fraction of titanium dioxide in the aluminum oxide film of the present invention affects the performance of the anti-reflection film; when the mass fraction of titanium dioxide in the aluminum oxide film is too small, the first average reflectivity will increase and the second average reflectivity will increase. This is because the TiO2 content in the outermost film is too small and the self-cleaning effect of TiO2 cannot be fully exerted; when the mass fraction of titanium dioxide in the aluminum oxide film is too large, the first average reflectivity will increase and the second average reflectivity will increase. This is because excessive TiO2 will inhibit the formation of a porous and loose structure on the surface of the Al2O3 film during the boiling process, and the anti-reflection effect will be weakened;

[0093] (3) By comparing Example 1 with Examples 8 and 9, it can be seen that the thickness of the aluminum oxide film in the present invention affects the performance of the anti-reflection film; when the thickness of the aluminum oxide film is too small, the first average reflectivity will increase and the second average reflectivity will increase. This is because if the aluminum oxide content is too small, it is difficult to grow a porous loose structure of sufficient thickness on the surface during the boiling process, and the anti-reflection effect is weakened; when the thickness of the aluminum oxide film is too large, the first average reflectivity will increase and the second average reflectivity will increase. This is because if the aluminum oxide content is too small, it will not match the thickness of the silicon oxide film layer, the interference destructive effect will be weakened, the spectrum will move toward the long-wave direction, and the visible light reflectivity will increase.

[0094] (4) By comparing Example 1 with Example 10, it can be seen that vacuum drying is beneficial to improving the environmental stability of the anti-reflection film. This is because vacuum drying can quickly remove moisture from the sample surface, forming a porous and loose aluminum oxide structure. The refractive index distribution is quite different from that of the sample dried in general, and the matching degree with the bottom layer is better, and the visible light reflectivity can reach an extremely low level.

[0095] (5) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the aluminum oxide film containing titanium dioxide stacked on the surface of the outermost interference film is beneficial to improving the environmental stability of the anti-reflection film. This is because titanium dioxide has self-cleaning properties and can decompose organic pollutants adsorbed on the surface under appropriate light, thereby improving the environmental stability.

[0096] In summary, the anti-reflection and anti-reflection film with environmental stability provided by the present invention can pass the environmental test well, and the reflectivity is always maintained below 0.1%. After the organic pollution test, the reflectivity of the anti-reflection and anti-reflection film changes little, and the reflectivity is continuously maintained below 0.1%. The anti-reflection and anti-reflection film has excellent environmental stability.

[0097] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. An anti-reflection and anti-reflection film with environmental stability, characterized in that: The anti-reflection and anti-reflection film comprises at least one layer of interference film which is stacked, and an aluminum oxide film containing titanium dioxide is stacked on the surface of the outermost interference film.

2. The antireflection film according to claim 1, characterized in that: The mass fraction of titanium dioxide in the aluminum oxide film is 1% to 10%.

3. The anti-reflection and anti-reflection film according to claim 1 or 2, characterized in that: The thickness of the aluminum oxide film is 30-40 nm.

4. The antireflection film according to any one of claims 1 to 3, characterized in that: The thickness of each layer of the interference film is independently 5 to 50 nm; Preferably, the anti-reflection and anti-reflection film includes four stacked interference films, and along the direction from away from the aluminum oxide film to close to the aluminum oxide film, the thickness of the four interference films are 5-15nm, 30-50nm, 1-10nm and 30-50nm respectively.

5. A method for preparing the anti-reflection and anti-reflection film according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The first deposition obtains at least one interference film, and the second deposition of an aluminum oxide film containing titanium dioxide is carried out on the surface of the outermost interference film. The film is dried after hydrothermal treatment to obtain an anti-reflection and anti-transmission film.

6. The preparation method according to claim 5, characterized in that: The first deposition and the second deposition each independently include atomic layer deposition.

7. The preparation method according to claim 5 or 6, characterized in that: The solution used in the hydrothermal treatment is water; Preferably, the pH of the solution used in the hydrothermal treatment is 5 to 8; Preferably, the temperature of the hydrothermal treatment is 50-90° C., and the time is 10-40 min.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The drying comprises vacuum drying; Preferably, the vacuum drying temperature is 0 to 85°C and the time is 10 to 60 minutes; Preferably, the vacuum degree of the vacuum drying is less than 10Pa.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method comprises: Atomic layer deposition is used to obtain at least one interference film, and an aluminum oxide film containing titanium dioxide is atomically deposited on the surface of the outermost interference film. After hydrothermal treatment for 10-40 minutes in water with a pH of 5-8 and a temperature of 50-90°C, vacuum drying is performed in an environment with a temperature of 0-85°C and a vacuum degree of less than 10Pa to obtain an anti-reflection and anti-transmission film.

10. An optical element, characterized in that: The optical element comprises the anti-reflection and anti-reflection film according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Preparing method of composite antireflective film through polytef and aluminum oxide atomic layer

    CN107337356A

  • Preparation method of tempered glass with abrasion-resistant aluminum oxide coating

    CN107793041A